Analisis Pengaruh Kesempatan Kerja, Belanja Bantuan Sosial dan Pertumbuhan Ekonomi terhadap Tingkat Kemiskinan di Provinsi Kalimantan Selatan - Nuraniah (PPJP ULM, 2019)
This research was conducted to see employment opportunities, social assistance spending, and economic growth related to poverty in Sout Kalimantan Province. The data used is the time series in 2007-2017, using multiple linear regression analysis. The study results are partially employment opportunity variables, social assistance spending, and growth affect poverty. In contrast, simultaneously, employment opportunity variables do not affect poverty, but social assistance spending and growth variables affect poverty in South Kalimantan Province.